Physclips III : Light : Final Report. - Wolfe, Joe (Office for Learning and Teaching, 2014)
Final report from a project that developed an extensive set of learning resources to cover the topic areas Light and other electromagnetic radiation, at the level of introductory university or senior high school. It adds a new volume to Physclips, a widely used and recommended electronic resource. For each chapter in this new volume, it includes a rich multimedia tutorial, supporting pages giving broader and deeper materials and laboratory exercises. Film clips, animations and their combinations are available for download by teachers. The various learning resources are all hyperlinked and offer extensive user control and indexing to facilitate their use in constructing a learning program to suit the learner, or for review, revision or research.